The Impact of Psychological Empowerment on Creative Behavior - - Derroum, Ahmed; Guehiri, Fatna; Hamiani, Sabrina (Finance and Business Economies Review, 2019)
The purpose of this study is to address the psychological empowerment and knowledge of the extent of its practice in the economic institutions in the state of Djelfa and measure the level of creative behavior, and try to know the impact of psychological empowerment on creative behavior, and to answer the main problem and test hypotheses was developed a questionnaire based on previous studies that addressed the variables, A random sample of 50 workers was selected from the dJelfa Mills Corporation. The results were based on the statistical program. The results of the study provided the level of availability of psychological empowerment in its dimensions and the creative behavior of the institution. And a positive impact on the dimensions of psychological empowerment (meaning, ability, influence, freedom) on creative behavior. And the impact of psychological empowerment on the creative behavior of the Jelfa Mills Corporation.